Workers’ Health in Brazil: Accidents recorded by Social Security from 2008 to 2014 - Josierton Cruz Bezerra; Luciano José Arantes; Helena Eri Shimizu; Edgar Merchán-Hamann; Walter Massa Ramalho (Revista Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to analyze the incidence of occupational accidents in Brazil, recorded by Social Security according to the geographic regions, age group, gender and their prevalence according to the causes and branch of economic activity. Methods: ecological descriptive study with time series analysis from 2008 to 2014. Data on the beginning and end of the historical series were compared in each ecological unit studied. Results: the South and Southeast regions, male, between 20 and 49 years of age presented the highest falls in incidence. 70.87% of the causes occurred in group XIX of ICD-10. The economic activity with the highest prevalence of accidents was the manufacturing industry. Conclusions: accidents at work have decreased in Brazil, however, the incidence is still high. Advances need to be made in the recording of accidents and in the prevention and surveillance of workers’ health.